2021
DOI: 10.1177/14614448211017920
|View full text |Cite
|
Sign up to set email alerts
|

Political discourses, ideologies, and online coalitions in the Brazilian Congress on Twitter during 2019

Abstract: The aim of this research is to describe the pattern of interactions of Brazilian legislators on Twitter during 2019 in the construction of political discourses. Based on 20,076 replies during 2019, posted on Twitter by 514 Brazilian legislators, we conducted descriptive analysis of legislators’ Twitter profiles, social network analyses from their interactions, and content analysis of the messages. We found that (1) there are large disparities between legislators in the use of Twitter; (2) the pattern of intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Just under two-thirds of these Twitter accounts are verified (293 out of 456), which we understand to be a valid proxy for validation as data collection predates the changes made to the Twitter verification system in November 2022. Informed by previous research that identified online coalitions in the Brazilian parliament (García-Sánchez et al, 2021), we annotated the data to identify user accounts affiliated with the government (GO), those of the opposition (OP), and those of the broad coalition known as Centrão (CE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just under two-thirds of these Twitter accounts are verified (293 out of 456), which we understand to be a valid proxy for validation as data collection predates the changes made to the Twitter verification system in November 2022. Informed by previous research that identified online coalitions in the Brazilian parliament (García-Sánchez et al, 2021), we annotated the data to identify user accounts affiliated with the government (GO), those of the opposition (OP), and those of the broad coalition known as Centrão (CE).…”
Section: Methodsmentioning
confidence: 99%
“…As such, an analysis of the insurrectionist playbook must be situated beyond the frames employed by the press to account for the narratives employed by the political campaign that cast doubt on the legitimacy of the electoral process. This can be achieved by monitoring the public statements of political elites, with previous research having effectively used Twitter to identify the discourse of Brazilian legislators and their political alignment (García-Sánchez et al, 2021).…”
Section: Previous Workmentioning
confidence: 99%
“…Just under two-thirds of these Twitter accounts are verified (293 out of 456), which we understand to be a valid proxy for authenticity as data collection predates the changes made to Twitter verification system in November 2022. Informed by previous research that identified online coalitions in the Brazilian parliament (García-Sánchez et al, 2021), we annotated the data to identify user accounts affiliated with the government (GO), those of the opposition (OP), and those of the broad coalition known as Centrão (CE).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, by encapsulating the ideas, values, and beliefs that exist within society and frame an individual’s worldview, ideology has important consequences for the shaping of broader social arrangements. Platforms are valuable vehicles for ideological discourse (García-Sánchez et al, 2021), constituting an arena across which social actors “struggle for recognition and attention, try to organize consent to their ideologies, and seek to influence how people think and behave” (Mirrlees, 2019: 28). And, as prominent sites of political expression and engagement (Ferrucci et al, 2020), platforms provide space for ideological tensions to play out (Bock and Figueroa, 2018).…”
Section: Platformization Ideology and Influencersmentioning
confidence: 99%